Կրկնությունը՝ որպես նույնաբանության գործաբանական ներուժը ձևավորող նախապայման - Արթուր Մեսրոպյան (ՀՀ ԳԱԱ հրատ.)
Статья посвящена изучению прагматического потенциала тавтологических высказываний в современном английском языке. Arthur Mesropyan in this article considers the pragmatic potential of nominal tautologies in Modern English.
Keywords: Philology; Linguistics; Language and Literature